2016
DOI: 10.1080/00343404.2016.1224334
|View full text |Cite
|
Sign up to set email alerts
|

From the urban university to universities in urban society

Abstract: The impacts of neoliberalization and the global extension of urbanization processes demand a reappraisal of the urban university for the 21 st century. The history of the modern urban university, and current calls for universities to assume proactive roles as economic drivers and civic leaders, disclose problematic tendencies, including: normalizing local/global binaries; focusing on a narrow set of university-city connections; and constructing the university and the city as monolithic rational agents. In resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 46 publications
(39 reference statements)
0
32
0
Order By: Relevance
“…The authors show how the development of urban space and urban infrastructure is carried out by the universities [18], how the lobbying takes place, and how the political support in the urban community is being received by the universities [19]. In addition, universities that have adopted the role of economic drivers and civic leaders, mitigate social contradictions that are present in the urban community [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors show how the development of urban space and urban infrastructure is carried out by the universities [18], how the lobbying takes place, and how the political support in the urban community is being received by the universities [19]. In addition, universities that have adopted the role of economic drivers and civic leaders, mitigate social contradictions that are present in the urban community [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, Castells and Hall (1994: 11), after reviewing some of the world-famous science spaces, concluded that 'most of the world's actual high-technology production and innovation still comes from … the great metropolitan areas of the industrialized world'. Little wonder, then, that specially designated science cities and parks of the campus-garden-suburb mould have become increasingly exposed to a change in the zeitgeist regarding the relationship between science and the city (Addie, 2016;Charles, 2015;Phelps et al, 2014).…”
Section: Between Planned City and Anonymous Suburbmentioning
confidence: 99%
“…As some of the evidence gathered above confirms, BSOs are still emerging and developing in cities, so their particular contribution to cities needs to be further, and more important systematically, assessed. Issues about public–private cooperation are central, but the role of research and education institutions, and universities first of all, cannot be underplayed (Addie, ). Functional questions also arise.…”
Section: Bsos and Urban Governance: Engagement Mandates And Impactmentioning
confidence: 99%